MENGUATKAN DAYA INGAT DALAM PEMBELAJARAN - Ahmad Rosidi (FKIP Universitas Islam Jember, 2015)
Achievement of memory can be owned if we had a concern in doing certain strategy and special effort. There are some ways to improve it. 1). Create the relationships logically and systematically. 2). A story can be a way to memorize. 3). ‘sleeping’ is a way to record the things we have learned 4). Associate something by the unusual thing 5). Use the real things to memorize abstract ideas 6). Designing tools by ourself is approach of memorizing . 7). Track back all the things that precede and accompany a forgotten incident 8). We need to have break for 2 to 5 minutes when we are studying in every 30 minutes 9). Repetition is an essential step in creating long-term memory. 10). Create a multy sensory memory by joining what we see, say and do. 11). Memorize the things by the acronym of the first letter of a word, phrase or sentence.Keyword : Memory